A Draft Standard Operating Procedures (SOPs) Manual Developed for Wollo University Institutional Research Ethics Review Committee (WU-IRERC): Ubuntu Philosophy Integrated for Multi-Disciplinary Research Ethics Review Framework, Wollo University, Ethiopia - Desalegn, Andualem Yimer (ORCID: 0000-0003-2609-2612) (ScienceOpen, 2025)
This preprint presents a comprehensive draft of the Standard Operating Procedures (SOP) manual developed for Wollo University Institutional Research Ethics Review committee. Fundamentally, this manual proposes an innovative shift in how we approach ethical review: it represents the first comprehensive integration of Ubuntu philosophy, emphasizing community interconnectedness and collective benefit, into the formal structures of institutional research oversight. Even though it was developed for Wollo University, the framework offers a scalable model for African academic institutions seeking to decolonize research methodologies while maintaining rigorous compliance with global standards. Moving beyond, the manual provides discipline-specific checklists tailored to the unique ethical landscapes of research in natural sciences, health & medicine, agriculture, environment & ecosystems, veterinary medicine, biomedical & biosciences, social sciences, engineering & informatics, and research in education & humanities. Crucially, we have harmonized these culturally grounded perspectives with strict regulatory requirements, ensuring full alignment with the Declaration of Helsinki, WHO guidelines, and Ethiopia’s National Research Ethics Proclamation (No. 1130/2019). The framework embodies several distinctive features. This framework includes innovative procedures for community impact assessment and establishes comprehensive protocols for human subjects research, animal studies, environmental investigations, and community-based inquiry. By centering Ubuntu philosophy as a core ethical principle, this manual doesn't just regulate research; it invites a more empathetic, culturally responsive approach to inquiry. The result is that it serves as a practical model for decolonizing research ethics governance in African universities, one that recognizes the profound responsibility toward the communities they serve and study. We hope this framework contributes as a practical roadmap for institutions aiming to honor more equitable, contextually responsive and ethically robust research practices across Africa
Keywords: African bioethics; Benefit-sharing; Community-based research; Ethiopian research guidelines; Institutional Research Ethics; Institutional Research Ethics Review Committee (IRERC); Multi-disciplinary research; Risk assessment; Standard Operating Procedures (SOPs); Ubuntu Philosophy; Wollo University